Hyper Sheets: Aplikasi E-Learning untuk Pembelajaran HTML dan CSS dengan menerapkan Konsep Gamification berbasis Web - Ivqonnada Al Mufarrih; Fajar Pradana; Fitra Abdurrachman Bachtiar (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2021)
The Massive Open Online Course (MOOC), which was supposed to revolutionize the world of education, did not happen as expected. MOOC registrants who survive to complete the course are very low, only around 2-11% of the total registrants. After being researched, the registrant's motivation plays a significant role in keeping the registrant following the given course to completion. Gamification is present as a solution to this problem. Gamification is a concept that applies game elements to something that is not a game to increase participants' motivation and engagement. In the context of this research, it applies to learning. Based on data from the Bureau of Labor Statistics in America, Web Developer jobs are projected to increase by 8% or about 14,000 new jobs, exceeding the average for other jobs in 2019-2029. The World Wide Web Consortium also said that HTML and CSS are the core technologies in creating the web. In response to this problem, an e-learning application was created for learning HTML and CSS by applying the concept of gamification, which was eventually named Hyper Sheets. The hope is that this application can maintain or even increase student motivation. The three main features of this app are interactive materials, exercises, and challenges. In developing this application, the Waterfall model is used, which finally gets 13 functional requirements and 1 non-functional requirement. The tests were carried out on functional requirements, namely unit testing with white box testing techniques and integration testing along with validation testing with black box testing techniques. These functional requirement tests get 100% valid results. In non-functional testing, namely usability testing, using the SUS method ultimately resulted in a score of 81.55. This score belongs to the "Acceptable" category, which is satisfactory to the application users.